ANALISIS YURIDIS TERHADAP PEMBATALAN AKTA SURAT KUASA YANG DIBUAT DENGAN AKTA NOTARIS TERKAIT DENGAN PERALIHAN HAK YANG OBJEKNYA DALAM JAMINAN BANK (STUDI PUTUSAN No. 445/PDT-G/2015/PN.Mdn Jo No. 49/Pdt/2017/PT.Mdn) - Rio Rinchy Siahaan (Jurnal Abdi Ilmu, 2022)
Decision on Case Number: 49/PDT/2017/PT.Medan which is an examination of the appeal level of Decision on Case Number 445/Pdt.G/2015/PN.Medan. The Panel of Judges carried out a deed of power related to the ownership of Property Rights Certificate Number 1085/Desa Seikambing B. Asmidar Chandry as the power of attorney to sue Zainurah (recipient of power of attorney), Head of the Land Office, and Notary/PPAT at the Medan District Court for violating the law. Results Based on the examination at the trial that the power of attorney was made in accordance with the provisions of the legislation. In fact, the power of attorney is made by the power of attorney on the basis of his will. Regarding this case, the problem is: How is the arrangement of the power of attorney made before a notary based on the laws and regulations? What is the accountability of the power of attorney made by a notary without the original document whose object is in his power as bank guarantee? What are the legal consequences for music Deed of power of attorney who listens with copyright? So that this research is entitled "Juridical Analysis of the Cancellation of the Deed of Power of Attorney Made with a Notary Deed Related to the Transfer of Rights whose object is in a Bank Guarantee (Decision Study Number 445/Pdt-G/2015/PN.Mdn Jo Number. 49/Pdt/ 2017) /PT.Mdn)” This type of research is normative legal research, namely research conducted by analyzing written laws from library materials or secondary data and reference materials in the field of law or references in the field of law. The data used to answer the problems in this research is secondary data that comes from library research. The power of attorney is basically regulated in the Civil Code although it is not explicitly explained about the power of attorney. The Civil Code regulates the granting of power of attorney and provisions for making a deed which is further regulated in the Law on Notary Positions. The notary is fully responsible for the correctness of the contents of the authentic deed. Notaries can also be subject to sanctions if in carrying out their profession in making actions that are not in accordance with the provisions stipulated in the Civil Code and the Law on Notary Positions. If the Notary makes a procedural error in making the deed as stipulated in the Civil Code and the Notary Position Act, the authentic deed becomes a private deed, it can be canceled or null and void by law. Even the parties who feel aggrieved can claim compensation from the Notary.